(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The Gelasian succession of the Capodarso area (Enna-Caltanissetta basin, Sicily, Italy) consists of an offlapping stack of cycles composed of siliciclastic units passing to carbonate heterozoan, clino-stratified wedges, developed from a growing positive tectonic structure. Identification of a number of facies tracts, based on sedimentary facies, biofacies and taphofacies, provided important information about the differentiation and characterisation of systems tracts and key stratal surfaces of sequence stratigraphy. The bulk of carbonate wedges are interpreted as representing the rapid falling-stage progradation of distally steepened ramps. The inferred highest rate of carbonate production during forced regressions was concomitant with active downramp resedimentation by storm-driven downwelling flows, leading to storing of most carbonate sediment on the ramp slope as clino-beds of the prograding bodies. Comparison of the Capodarso ramps with other icehouse carbonate ramps, with particular regard to the Mediterranean Plio-Pleistocene, provides clues for defining some common features. These are inferred to include: (1) brief, rapid episodes of progradation concomitant with orbitally-forced sea-level changes, resulting in limited ramp width; (2) preferential fostering of growth and downramp resedimentation of heterozoan carbonates during glacial hemicycles marked by enhanced atmospheric and marine circulation; (3) building out from positive features of entirely submerged distally-steepened ramps with storm-wave-graded profile and distinctive clinoforms; (4) ramp stacks generally consisting of mixed clastic-carbonate sequences showing an ordered spectrum of distinct frequencies; (5) rapid, continuous changes in environmental parameters, leading to the short-lived persistence of faunal communities, climax communities generally having insufficient time to form.